Natural vs. anthropogenic metals for reconstructing the source-to-sink pathway (Naples Bay, eastern Tyrrhenian Sea) - Milia, Alfonsa; Buonocunto, Francesco Paolo; Mali, Matilda; Giandomenico, Santina; Leo, Antonella Di; Spada, Lucia; Ferraro, Luciana; Giordano, Laura (Frontiers in Earth Science, 2023)
The grain size, nutrients, and metals contents of sediments are important tracers for reconstructing the origin of the contaminants and the pathway of the sediments from the source to the sink. This is particularly important in areas with high geological variability and a high demographic pressure. The origin and distribution of contaminants and nutrients allow us to identify the source-to-sink pathway of the sediments. In particular, the Sarno River is one of the main contributing sources of anthropogenic contaminants due to the outflow from the large surrounding large industrial area. Geochemical and physical parameters of sediments were analyzed along a transect from the coastline to a water depth of 112 m, with the objective of exploring the spatial variability of sediment contamination in the continental shelf of Naples Bay. The latter is characterized by a complex geological area and is subject to river inflow from a highly industrialized area. The data have been analyzed using principal component analysis (PCA), hierarchical correlation analysis (CA), and analysis of variance (ANOVA). To distinguish between a natural and anthropogenic origin of contaminants and to construct the source-to-sink pathway, the relationship between geochemical and physical data and their distribution was examined, and the results were compared with published data collected onshore. Four distinct sectors with different associations of metals, grain size, and total organic carbon have been recognized: I) offshore Vesuvius volcano, the occurrence of coarse-grained sediments, associated with As, Fe, Mn, and low TOC values, suggests a natural origin of the contaminant due to the volcanic nature of the substrate; II) offshore the Sarno River, the presence of Cr, Cd, Cu, Pb and Zn, associated with the high TOC content, suggests an anthropogenic origin for the contaminants; III) offshore Sorrento Peninsula, the presence of As, Fe, Mn, and some gravel made up of pumice and bioclasts indicate a predominance of contaminants of natural origin; and IV) finally, the distal part is not subjected to a primary terrestrial input. Metals contamination of anthropogenic origin and the organic matter in sediments decreased rapidly with distance from the coast highlighting the main deposition area close to the river discharge.